STOCK PRICE MOVEMENT AND VOLATILITY IN MUSCAT SECURITY MARKET (MSM) - Husain, Uvesh; Javed, Sarfaraz (International Journal of Research -GRANTHAALAYAH, 2019)
This paper examines the stock price movement and volatility in listed financial Omani Companies in MSM. The study made use of secondary data. This study is an attempt to answer these important questions, is there an effect of the announcement of the dividend policy on the market value of the shares of the Omani companies listed in MSM? Moreover, Is there any effect for each of the announcement of the earnings per share and distribution of profits on the market value of the shares of the Omani companies listed in MS at the level of each year of the study? The analytical descriptive approach was used to investigate. This study mainly depends on secondary data. The event study methodology is intended to investigate the effect of an event on a specific dependent variable. An “event” is the public announcement of a (usually voluntary) corporate action. In this considered corporate action is the dividend announcement. The abnormal return is calculated form 10 days prior to the event and 10 days post to the event.